General characteristics of the means obtained from species belonging to the genus Trichoderma Karst distributed in Azerbaijan - P.Z., Muradov; K.F., Bakhshaliyeva; M.Kh., Mamedaliyeva; M.H., Maharramova; F.T., Aliyev; K.K., Isayeva; G.A., Tomuyeva (Edelweiss Applied Science and Technology, 2025)
In the conducted studies, 72 species belonging to sac fungi were isolated from the soil used for the cultivation of fruits and berries in pure culture. It became clear that among the recorded fungi, there are species that have antagonistic relationships with each other. Among these species, fungi belonging to the genus Trichoderma were observed with higher activity, with the highest activity recorded in species identified as Trichoderma asperellum and T. harzianum using classical methods. After identification through molecular techniques, it was found that the cultural solution obtained from the 5-day cultivation of the T. harzianum AEF-2024 strain on solid nutrient medium was suitable for research purposes. When diluted 50 times, this solution had the maximum effect on increasing the germination rate of various plant seeds. This finding opens wide prospects for using it to enhance the productivity of various plants (such as peas, tomatoes, wheat, etc.), especially those propagated by seeds.